Heat-sensitive Step in Deoxyribonucleic Acidmediated Transformation of Bacillus subtilis - McCarthy, Charlotte (1969)
Over 90% of the competent cells in a population of Bacillus subtilis lost their competence after being heated to 50 C for 5 min. There was only a slight loss in the number of transformants if the culture was heated for 5 min after the termination of transformation, but 90% of the transformants were lost after 1 hr at 50 C. The population as a whole grew at a slightly faster rate at 50 C than at 32 C. We postulate that a heat-labile factor is required for the uptake or retention (or both) of deoxyribonucleic acid (DNA) in the cell, since uptake of (32)P-DNA into a deoxyribonuclease-resistant form was inversely proportional to the time of exposure to heat. Cells that had lost competence after being heated did not regain their competence for at least several hours, although other cells in the population became competent. These data suggest that the heat-labile factor required for competence is synthesized only once during the period that a cell remains competent.